6y+t(6y+3)=16

Simple and best practice solution for 6y+t(6y+3)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+t(6y+3)=16 equation:


Simplifying
6y + t(6y + 3) = 16

Reorder the terms:
6y + t(3 + 6y) = 16
6y + (3 * t + 6y * t) = 16
6y + (3t + 6ty) = 16

Reorder the terms:
3t + 6ty + 6y = 16

Solving
3t + 6ty + 6y = 16

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6y' to each side of the equation.
3t + 6ty + 6y + -6y = 16 + -6y

Combine like terms: 6y + -6y = 0
3t + 6ty + 0 = 16 + -6y
3t + 6ty = 16 + -6y

Reorder the terms:
-16 + 3t + 6ty + 6y = 16 + -6y + -16 + 6y

Reorder the terms:
-16 + 3t + 6ty + 6y = 16 + -16 + -6y + 6y

Combine like terms: 16 + -16 = 0
-16 + 3t + 6ty + 6y = 0 + -6y + 6y
-16 + 3t + 6ty + 6y = -6y + 6y

Combine like terms: -6y + 6y = 0
-16 + 3t + 6ty + 6y = 0

The solution to this equation could not be determined.

See similar equations:

| 4g^2-25g+6=0 | | 5(x+4)+2x=-2(x+3) | | -13+b=33 | | q=(4q-6n)/(3m)f | | (x-5)^2/3-2= | | 4c+3D=37 | | (X-2)(x-4i)(x-4i)=0 | | 3x+2y=13-2x | | -2-3/(-1)x8 | | a-7b+a-3b= | | F(x)=3x^2-12x-4 | | 5p-4p=-21-7 | | -9x+7=-6x+37 | | 2x=5-1 | | 9x-6=14x+19 | | -15x+6=-10x+16 | | 2x-7y+x+4y= | | 4x+2x(1+4)=36 | | http://media.edgenuity.com/evresources/3108-05-09/mc017-1.jpg | | s=t+8 | | t+2s=-5 | | 2(4x+3)=3x-(2x+4) | | 162=2x+1(2)+2x | | 500=x^3+25x | | 4x+10+8x+12=12 | | 10(6x-2x+x)=1000 | | 3/11-4/7 | | 2/t=5/t-6 | | 55296=2x(x^2-4x-32) | | X+a=14 | | X=a=14/ | | 4x-3(2)+2x=114 |

Equations solver categories